The role of ethics for the audit profession in achieving audit quality field research in a sample of audit offices operating in Iraq (Entrepreneurship Journal for Finance and Business, 2021)
The aim of the research is to provide a theoretical introduction to the ethics of the auditing profession with a review of the role of ethics in the auditing profession in achieving and enhancing the quality of auditing for auditors working in a sample of audit offices operating in Iraq, as the sample consisted of (50) auditor offices, and to achieve the research objectives, the two researchers prepared a questionnaire It included (25) items, and they were analyzed using the statistical program (SPSS). The two researchers reached a number of results, the most prominent of which are:1. There is a high commitment of the auditor in Iraq to the ethical codes of the auditing profession, which contributed to achieving the quality of auditing.2. The ethical codes of auditing profession adopted in Iraq do not fully contribute to the economic and social welfare of society.3. There is a statistically significant relationship between the auditors ’commitment to ethical behavior and the quality of the audit work, as the responses of the research sample showed a clear agreement on the existence of the relationship.In light of this, a number of recommendations were presented, the most important of which are:1. The necessity for the Board of Auditing and Auditing Profession in Iraq to hold sessions and seminars dealing with the rules of ethical behavior, especially with regard to honesty and avoiding personal judgments and whims, except within narrow and professionally justified limits.2. The necessity of activating the role of monitoring committees in the auditing profession council to perform its supervisory role on all aspects of auditing, especially limiting the negative impacts of the beneficiaries on auditing processes.3. The need to pay attention to the dimension of professional requirements by setting policies and procedures that affirm and commit the auditor to adhere to the principles of independence, objectivity and integrity